(untitled) (Indian Journal of Public Health Research & Development, 2021)
Better understanding by mapping picturesque thematic information, and visualizing the actual burden of arthropod vector borne disease vertically and horizontally, using GIS, analytical cartographic and geovisualization methods guide to select an appropriate methods for control and management of the disease. Both, the site specific public health epidemiology and entomological reality information on the grounds could be collected with GPS, and could be mapped under the GIS techniques. Different type of field survey methods and techniques could have been functional for the study of arthropod vectors surveillance, especially, mosquitoes, ticks, and mites vector abundance, and ecology, must have been essentially needed revision and updates for the achievements of goal move towards the betterment of vector borne disease control and management. Probability sampling (random sampling, systematic sampling, stratified sampling), and Nonprobability sampling (convenience sampling, snowball sampling, quota sampling) existing conventional survey methods have been replaced with GIS scientific methods, used for public health epidemiological studies, and arthropod entomological study as well. Applied GIS contains the methods and techniques used for different field survey, such as; a systematic grid sampling techniques, GIS and GPS based reconnaissance survey methods, cluster sampling, stratified sampling, multistage sampling pilot sampling and random sampling survey with i) physiographic landscapes, ii) climate zones, iii) socio-economic structures, iv) settlement structures, v) land use / land cover categories, and vi) sampling survey in the buffering zones, etc., provides the accurate geo-coordinates site specific approach to portray the diversity and reliability of arthropod vector presents, and geovisualization of the vertical and longitudinal pattern of vector profusion, and thus, researcher and planners could be formed a datum of guidelines for arthropod vectors surveillance, and hence, preparing the indispensable prevention measures to vector borne disease control and management for sustainable health.